2009
DOI: 10.3945/ajcn.2009.27799
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein and bone health: a systematic review and meta-analysis

Abstract: A small positive effect of protein supplementation on lumbar spine BMD in randomized placebo-controlled trials supports the positive association between protein intake and bone health found in cross-sectional surveys. However, these results were not supported by cohort study findings for hip fracture risk. Any effects found were small and had 95% CIs that were close to zero. Therefore, there is a small benefit of protein on bone health, but the benefit may not necessarily translate into reduced fracture risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
223
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(235 citation statements)
references
References 76 publications
4
223
1
7
Order By: Relevance
“…Depending on measurement site, dietary factors, including total energy intake and dietary intakes of protein, Ca, vitamin D and K, strengthened or attenuated the association between alcohol and BMD. The latter have been identified as the most evident dietary factors affecting BMD in the literature (37)(38)(39)(40)(41) and were therefore added to the analysis. These findings suggest that low alcohol consumption has an independent effect on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on measurement site, dietary factors, including total energy intake and dietary intakes of protein, Ca, vitamin D and K, strengthened or attenuated the association between alcohol and BMD. The latter have been identified as the most evident dietary factors affecting BMD in the literature (37)(38)(39)(40)(41) and were therefore added to the analysis. These findings suggest that low alcohol consumption has an independent effect on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…43 A number of meta-analyses have questioned the hypothesis that the diet net acid load reduces bone mass. 10,47,48,49 Mean estimated dietary NEAP is in the order of þ 40 mEq/day, whereas estimated urinary PRAL is low. If these women were eating generally healthy diets, although dietary acidity was positive, it was perhaps insufficiently acidic enough (as indicated by the negative urinary PRAL) so that the additional alkaline-generating potassium salts did not benefit BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, dietary protein is a source of metabolic acid that may lower the pH of urine and increase urinary calcium excretion, which could lower bone mass,3 although a meta‐analyses of randomized trials reported that higher protein intakes are not detrimental to calcium retention or bone mineral loss 4. A systematic review on the relationship between protein and bone health reported no adverse associations between protein intake and bone mineral density (BMD) and a meta‐analysis of six randomized controlled trials showed a beneficial effect of protein supplementation (40 mg of milk basic protein or 20.4 g total protein) on lumbar spine BMD of 0.02 g/cm 2 5. A number of cross‐sectional and prospective studies have also reported associations between higher total protein intake and higher BMD in women 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%